2020
DOI: 10.3390/ijms21051892
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Grade-Dependent Mapping of Metabolic Landscapes in Human Urothelial Bladder Cancer: Identification of Novel, Diagnostic, and Druggable Biomarkers

Abstract: Background: Urothelial bladder cancer (UBC) is one of the cancers with the highest mortality rate and prevalence worldwide; however, the clinical management of the disease remains challenging. Metabolomics has emerged as a powerful tool with beneficial applications in cancer biology and thus can provide new insights on the underlying mechanisms of UBC progression and/or reveal novel diagnostic and therapeutic schemes. Methods: A collection of four human UBC cell lines that critically reflect the different mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Occupational factors are considered the second most important risk factor for BC [3]. Workers exposed to aromatic amines, polycyclic aromatic hydrocarbons, tobacco and tobacco smoke, combustion products, and heavy metals are at an increased risk [4].…”
Section: Introductionmentioning
confidence: 99%
“…Occupational factors are considered the second most important risk factor for BC [3]. Workers exposed to aromatic amines, polycyclic aromatic hydrocarbons, tobacco and tobacco smoke, combustion products, and heavy metals are at an increased risk [4].…”
Section: Introductionmentioning
confidence: 99%
“…Two conjectures accounted for the conflicting IHC results. DE between ADAMTS12 at the transcriptional and translational levels had been neglected before experimental design; T24, EJ, and 5637 cell lines were recently applied in studies exploring the invasive, progressive, and metastatic capabilities of advanced BCa, suggesting that they could be viewed as high-grade BCa cells (ACS-BCa) ( 45 47 ). This also supported the inconsistent expression of CDH11 in 5637, and COL6A1 in EJ and 5637, cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted though that the link between the tumor grade and energy-related metabolic profiles is more complex. For example, a study of metabotypes of urothelial bladder cancer cell lines of different grades indicated that metabolic pattern for grade I cells (RT4) is more similar to grade IV (more advanced tumors) than grade III [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found a cancer cell line, RT4, expressing high levels of ALDH1L1. These cells were derived from a grade I urothelial carcinoma and they represent a low-grade bladder cancer [ 22 , 23 , 24 ]. Our previous [ 25 ] experiments confirmed presence of high levels of ALDH1L1 in these cells.…”
Section: Introductionmentioning
confidence: 99%